Use of patient simulators to characterize the repeatability and reproducibility of automated oscillometric blood pressure monitors. Issue 5 (October 2018) - Sarhrani, Elmiloudi M.; Gilmore, Thomas B.; Lamontagne, Andre S.; Harris, Lauren B.; Kellett, Jay S.; Sweeney, Michael P.; Navas, Teresa I.; Vesnovsky, Oleg; Ho, Charles; Herbertson, Luke H.
Abstract : Objectives: Automated oscillometric blood pressure (BP) monitors can be critical health assessment tools if they are accurate and can provide repeatable and reproducible readings. Commercial patient simulators are capable of screening for poorly performing oscillometric BP monitors. A valid screening bench test method to identify unreliable and underperforming BP monitors could advance surveillance of these devices and support regulatory decision making. Methods: Two simulators were used to characterize a total of 19 legally marketed upper arm, wrist, hospital-grade, and public-use BP monitors. These oscillometric BP monitors were tested for repeatability and reproducibility across different simulated patient populations. The metrics for evaluating these devices were the difference between the simulated pressure and the BP monitor output, and the variability from repeated measurements. Results: All but one of the BP monitors tested provided repeatable readings (<3 mmHg). The mean error between the simulated pressure and the BP monitor output was largest for the wrist devices, whereas hospital-grade BP monitors most closely estimated the target BP waveforms. In general, device error and measurement variability increased at elevated BPs. Conclusion: Patient simulators are more suitable for repeatability analysis as opposed to assessing device accuracy. Despite their limitations, patient simulators can be used as effective tools to screen and improve the quality of BP monitors.